Pengaruh Model Pembelajaran Kooperatif dan Gaya Belajar Kolb terhadap Hasil Belajar Dasar-Dasar Ilmu Politik - Sugiharto - (JTP - Jurnal Teknologi Pendidikan, 2014)
The aims of this research were to determine the effect of cooperative learning model and learning styles on learning the result. This quasi-experimental study employed a 2X2 treatment by level, involving cooperative learning model and learning styles as independent variables, and learning result as the dependent variable. Research findings show that: (1) students’ learning result who were taught by cooperative learning model type of GI were higher compared to those that based on type STAD. (2) there was an effect of interaction between cooperative model and learning styles on the students’ learning result. (3) the learning result of the type of accommodator students who were taught by learning model type of GI was higher than those who were taught by type of STAD. (4) The assimilators learning results who were taught by type of GI were lesser than those of STAD’s.